King's dream - Sundquist, Eric J. (Icons of America., 2009)
In this new exploration of the "I Have a Dream" speech, Sundquist places it in the history of American debates about racial justice and demonstrates how the speech, an exultant blend of grand poetry and powerful elocution, perfectly expresses the story of African-American freedom